If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -4(2a + 7) = 74 Reorder the terms: 6 + -4(7 + 2a) = 74 6 + (7 * -4 + 2a * -4) = 74 6 + (-28 + -8a) = 74 Combine like terms: 6 + -28 = -22 -22 + -8a = 74 Solving -22 + -8a = 74 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + -8a = 74 + 22 Combine like terms: -22 + 22 = 0 0 + -8a = 74 + 22 -8a = 74 + 22 Combine like terms: 74 + 22 = 96 -8a = 96 Divide each side by '-8'. a = -12 Simplifying a = -12
| V-2.9=-4.422 | | 8b-7=-7+3b+4b | | -10.5+m=-2.748 | | 4nxp= | | 4x(x-5)=4x-35 | | -6q=q-35 | | -60+12x-7x=30 | | 9(4+t)-7(t+3)= | | -23-6x=-3x+52 | | m-4.9=-7.11 | | 1x(3)=2y+1 | | s=3f-22 | | 4b-6=22 | | -7n^2-9n-8=0 | | 9k+5=48 | | f(t)=-3t+4 | | 2(x+5)=6(3) | | r-7=2r | | 3x+-4=3+2x | | -26.7+3.4x=4.4(x-6) | | 24x-4=6 | | 3(3n-1)=12 | | X-8+x-3x=64 | | 3x+36= | | 2x-8x-131=37 | | 4+3x=9+3x | | -4k+4k=-6k | | 11-7n=-7n+8+3 | | 7h+-9=-2 | | 12x-10= | | 6.8x-10.4=6x+4 | | 8x-6x-9=-x+3 |